2013
DOI: 10.1093/her/cyt044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a web-based stroke education program on recurrence prevention behaviors among stroke patients: a pilot study

Abstract: The effectiveness of methods to prevent stroke recurrence and of education focusing on learners' needs has not been fully explored. The aims of this study were to assess the effects of such interventions among stroke patients and their primary caregivers and to evaluate the feasibility of a web-based stroke education program. The participants were 36 patients with a clinical diagnosis of ischemic stroke within 12 months post-stroke and their primary caregivers. The participants were randomly assigned to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
129
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(134 citation statements)
references
References 38 publications
4
129
0
1
Order By: Relevance
“…9,10,13,14,17,18 One large study used cluster randomization by unit. 11 The remaining three studies were quasi-experimental (e.g., non-random assignment to condition 12,16 or single group 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…9,10,13,14,17,18 One large study used cluster randomization by unit. 11 The remaining three studies were quasi-experimental (e.g., non-random assignment to condition 12,16 or single group 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…11 Five studies had sample sizes of less than 50. 10,12,14,15,17 These studies should be interpreted with caution, particularly since small pilot studies do not provide meaningful effect size estimates for larger studies, let alone enough power for hypothesis testing. 19 Some smaller studies reported statistically significant results, which could have resulted from Type I error.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations